Wskaźniki oceny działalności handlu - Zakrzewski, Zbigniew (Wydział Prawa i Administracji UAM, 1970)
When fixing indices to estimate commercial activity one should take account of only such phenomena in the field of goods traffic that can be conceived quantitatively and intercepted. It may be useful to isolate first of all the group of segmental indices of the nature of value to explain if and to what extent the trade meets the consumers' demands. The most important index belonging to that group is the one that determines how the trade acquits itself of the function of coordinating demand and supply in the respect of commodity assortment. Apart from an attempt to estimate to what extent the trade meets consumers' demands as regards the kind, quantity, quality, place and way of supplying the ultimate consumers with various goods it is necessary to determine with appropriate indices to what extent the trade acquits itself of its tasks for industry, agriculture accumulation, monetary policy, etc. Only such a broad system of indices gives a full picture of the commercial activity. Up to this time no compact system of analyses nas been created to estimate the trade in all its aspects.
Indices for Estimation of Commercial Activity